Assessment and Treatment of a Young Adult with Congenital Heart Disease and ADHD. Issue 4 (May 2021) - Hammerness, Paul G.; Cassidy, Adam R.; Potts, Heather; Richardson, Alanna; Fogler, Jason; Daly, Kevin P.; Augustyn, Marilyn
Abstract : CASE: : Phillip is a young man born with hypoplastic left heart syndrome referred to your practice for a range of mental health concerns. He underwent palliation to an extracardiac Fontan in infancy and experienced multiple complications over the next decade including valvular regurgitation and arrhythmias necessitating a pacemaker. Phillip continued to have systolic heart failure with New York Heart Association class II symptoms, managed with 4 medications and anticoagulation. Despite this complex history, Phillip had intact cognitive abilities, achieved typical milestones, and performed well academically in secondary school. His first year of college proved to be more challenging, and Phillip presented to the outpatient psychiatry service with an acute depressive episode. His family history included depression, without known attention-deficit/hyperactivity disorder (ADHD). Treatment, including a selective serotonin reuptake inhibitor, cognitive behavioral therapy, and family support, led to near resolution of his symptoms of depression. In subsequent appointments, Phillip described a long history of inattention and disorganization with onset in childhood. This contributed to the decision to leave college, despite remission of symptoms of depression. Phillip was unable to study for any extended period without "perfect conditions, " described as the absence of potential distractions except for background music. Despite attempts to maintain "perfect conditions, " Phillip was often off task and "hyperfocusing" on irrelevant topics. Phillip struggled with planning and time management and would misplace items daily. Moreover, although the importance of self-care was well understood, Phillip often forgot to take his cardiac medication or to exercise, and he admitted to inconsistent sleep habits because of losing track of time. Based on a comprehensive psychiatric evaluation including retrospective report from a parent, Phillip was diagnosed with ADHD, coexisting with major depressive disorder, in remission. Significant ADHD symptoms were documented by interview, self-report, and administration of an abbreviated neuropsychological battery. Considering concerns regarding use of stimulants in a patient with congenital heart disease, including death, stroke, and myocardial infarction, 1, 2 how would you assess the risks-benefits of use of stimulants with Phillip? REFERENCES: 1. Wilens TE, Prince JB, Spencer TJ, et al. Stimulants and sudden death: what is a physician to do? Pediatrics. 2006;118:1215–1219. 2. Zito JM, Burcu M. Stimulants and pediatric cardiovascular risk. J Child Adolesc Psychopharmacol. 2017;27:538–545.